Immune reconstitution inflammatory syndrome (IRIS) in a patient with neuro pulmonary nocardiosis following hematopoietic cells transplantation (HCT). Issue 2 (February 2022) - Gur, Ivan; Petersiel, Neta; Karban, Amir; Zuckerman, Tzila; Oren, Ilana; Stern, Anat
Abstract: Immune reconstitution inflammatory syndrome (IRIS) is increasingly reported in various HIV negative patients with immunosuppression, but the relationship with hematopoietic cell transplantation (HCT) is not well defined. We report a case of IRIS in a patient infected with pulmonary and CNS Nocardiosis following HCT due to primary myelofibrosis.